2020
DOI: 10.1063/5.0023526
|View full text |Cite
|
Sign up to set email alerts
|

The effect of one-atom substitution on the photophysical properties and electron spin polarization: Intersystem crossing of compact orthogonal perylene/phenoxazine electron donor/acceptor dyad

Abstract: A perylene (Pery)–phenoxazine (PXZ) compact orthogonal electron donor/acceptor dyad was prepared to study the relationship between the molecular structures and the spin–orbit charge transfer intersystem crossing (SOCT-ISC), as well as the electron spin selectivity of the ISC process. The geometry of Pery–PXZ (80.0°) is different from the previously reported perylene–phenothiazine dyad (Pery–PTZ, 91.5°), although there is only one atom variation for the two dyads. Pery–PXZ shows a high singlet oxygen quantum yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 113 publications
3
33
0
Order By: Relevance
“…Moreover, we found that the electron spin selectivity of SOCT-ISC is not only dependent on the conformation of the dyads, as previously found, but also on the structure of the electron donor . The effect of one-atom substitution on the photophysical properties and electron spin polarization (ESP) was only reported in perylene-PXZ and perylene-phenothiazine (PTZ) compact dyads. , …”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, we found that the electron spin selectivity of SOCT-ISC is not only dependent on the conformation of the dyads, as previously found, but also on the structure of the electron donor . The effect of one-atom substitution on the photophysical properties and electron spin polarization (ESP) was only reported in perylene-PXZ and perylene-phenothiazine (PTZ) compact dyads. , …”
Section: Introductionsupporting
confidence: 70%
“…Some compact orthogonal dyads showing efficient SOCT-ISC have been reported. ,, However, there are still some challenges for the investigation of SOCT-ISC; for instance, the chromophores used for SOCT-ISC are limited. The majority of the reported studies are focused on chromophores such as naphthaleneimide, , Bodipy, , rhodamine, , and perylene bisimide. , Perylene-3,4-dicarboximide (PMI) has been widely used in various fields of photochemistry. Recently, we reported N -(2,6-diisopropylphenyl)-perylene-3,4-dicarboximide - phenothiazine ( PMI–PTZ ) dyads; moderate ISC was observed, and the singlet oxygen quantum yield (Φ Δ ) was 57%.…”
Section: Introductionmentioning
confidence: 99%
“…However, to fully understand the SOCT-ISC efficiency as well as the electron spin selectivity of the ISC of these dyads, more examples are required. For instance, the spin dynamics of some systems are studied by time-resolved electron paramagnetic resonance (TREPR) spectroscopy. ,, It was proposed that the electron spin polarization (ESP) pattern of the TREPR spectra of the triplet state accessed by SOCT-ISC is always different than the conventional SO-ISC mechanism. ,, This is true but only for few cases: we found that the ESP pattern of the triplet TREPR spectra can be the same for both the mechanisms (SOCT-ISC and SO-ISC) and it is also dependent on the structures of electron donors/acceptors. ,,, Moreover, the effect of the mutual orientation of electron donor and acceptor chromophores on the SOCT-ISC efficiency and the electron spin selectivity was rarely studied.…”
Section: Introductionmentioning
confidence: 88%
“…27,31,35 This is true but only for few cases: we found that the ESP pattern of the triplet TREPR spectra can be the same for both the mechanisms (SOCT-ISC and SO-ISC) and it is also dependent on the structures of electron donors/acceptors. 30,36,38,39 Moreover, the effect of the mutual orientation of electron donor and acceptor chromophores on the SOCT-ISC efficiency and the electron spin selectivity was rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the triplet state of Rho-Pery-1 is localized on the perylene unit. We also prepared compact orthogonal electron donor–acceptor dyads with perylene unit as either electron donor or as electron acceptor. , The D and E parameters of the triplet state were determined as ca. 59.6 mT and 2.1 mT, respectively.…”
Section: Discussionmentioning
confidence: 99%